2019
DOI: 10.1302/0301-620x.101b9.bjj-2018-1115.r2
|View full text |Cite
|
Sign up to set email alerts
|

Tibial nailing using a suprapatellar rather than an infrapatellar approach significantly reduces anterior knee pain postoperatively: a multicentre clinical trial

Abstract: Aims The aim of this study was to compare the incidence of anterior knee pain after antegrade tibial nailing using suprapatellar and infrapatellar surgical approaches Patients and Methods A total of 95 patients with a tibial fracture requiring an intramedullary nail were randomized to treatment using a supra- or infrapatellar approach. Anterior knee pain was assessed at four and six months, and one year postoperatively, using the Aberdeen Weightbearing Test – Knee (AWT-K) score and a visual analogue scale (VAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 28 publications
2
59
0
Order By: Relevance
“…This study demonstrated that the VAS pain score was significantly lower in the SP group than in the IP group. This finding is consistent with the finding observed in a multicenter clinical trial conducted by MacDonald et al who compared the VAS scores between the IP and SP approaches in 95 patients and demonstrated that the SP IMN surgical approach is associated with lower postoperative anterior knee pain than that associated with the IP IMN surgical approach [19]. A recent meta-analysis indicated that the SP approach was associated with a significant reduction in the VAS scores [17].…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrated that the VAS pain score was significantly lower in the SP group than in the IP group. This finding is consistent with the finding observed in a multicenter clinical trial conducted by MacDonald et al who compared the VAS scores between the IP and SP approaches in 95 patients and demonstrated that the SP IMN surgical approach is associated with lower postoperative anterior knee pain than that associated with the IP IMN surgical approach [19]. A recent meta-analysis indicated that the SP approach was associated with a significant reduction in the VAS scores [17].…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrated that the VAS pain score was signi cantly lower in the SP group than in the IP group. This nding is consistent with the nding observed in a multicenter clinical trial conducted by MacDonald et al who compared the VAS scores between the IP and SP approaches in 95 patients and demonstrated that the SP IMN surgical approach is associated with lower postoperative anterior knee pain than that associated with the IP IMN surgical approach [19]. A recent meta-analysis indicated that the SP approach was associated with a signi cant reduction in the VAS scores [17].…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the RCTs have low risk of bias in terms of randomisation, allocation concealment, incomplete outcome data and selective outcome reporting, whereas some studies demonstrated high levels of bias in terms of blinding of participants and outcome assessment [7,15,21]. The risk of bias graph and summary are displayed in Figs.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The median follow up time periods for each study ranged from 9 months to 50.4 months. Post-operative knee function was assessed with the Lysholm knee score in four studies [7,15,21,23]. the Hospital for Special Knee Surgery Score (HSS) in 2 studies [17,20], Kujala Knee Score in 2 studies [19,23] and Oxford Knee Score (OKS) in one study [16].…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation